Local variation in helminth burdens of Egyptian spiny mice (Acomys cahirinus dimidiatus) from ecologically similar sites: relationships with hormone concentrations and social behaviour - Barnard, C.J.; Sayed, E.; Barnard, L.E.; Behnke, J.M.; Abdel Nabi, I.; Sherif, N.; Shutt, A.; Zalat, S. (Cambridge University Press, 2003)
Populations of Egyptian spiny mice (Acomys cahirinus dimidiatus) in a fragmented montane wadi system in the Sinai showed significant differences in the abundance of gut helminths. Differences in parasite load between populations were positively associated with measures of androgen activity but showed no significant relationship with glucocorticoid activity. Social discrimination tests with adult males from different wadis showed that those from sites with greater helminth abundance were less likely to investigate odours from other males and were less aggressive when subsequently interacting with the odour donors. Subjects showed markedly more investigation towards the odours of males from distant wadis compared with those from their own or immediately neighbouring wadi, but were less aggressive when confronted with odour donors from distant wadis. Despite this, there was a positive relationship between the amount of investigation towards distant male odour and subsequent aggression towards the male. While aggressiveness was positively associated with measures of androgen and glucocorticoid activity, no significant relationship emerged with individual helminth infection. Thus aggressiveness appeared to relate to overall local population levels of infection rather than individual challenge.